Pengaruh Media Board Game Terhadap Hasil Belajar Siswa Pada Pembelajaran Matematika Kelas II Sekolah Dasar - Ayu Ilmiyah, Elina; Susilo, Tri Achmad Budi; Maqfiro, Mochammad Ludfy Hadis (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
Mathematics learning is compulsory learning at every level of eduction. The low understanding of students during mathematics learing can produce suboptimal learning outcomes. The gives significant confidence for researchers to use board game media in examining research problems. The purpose of conducting research using quantitative experimental methods that apply a Nonequivalent Control Group design aims to determine whether or not there is an influence of board game media on student learning outcomes in grade II elementary school mathematics learning. The instrument used are pretest, posttest and student response questionnaires. There is a difference in the average learning outcomes in the experimental class obtained a value of 90,66 while in the control class obtained a value of 62,66. The results of the test t (4,315) > t table (2,160) with a p-value of 0,001 < 0,05 which means H0 is rejected. Then the results of the student response questionnaire in learning using the board game media are 82%.